Unsur Kualitas Layanan dan Nilai Pelanggan sebagai Pembentuk Kepuasan Pelanggan di PT Bank BNI 1946 Cabang UPI Bandung - Mulyadi, Ajang (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2022)
AbstractThe aim of this research is to determine and analyze the service quality of PT Bank BNI Branch Office UPI Bandung, the customer value of PT Bank BNI Branch Office UPI Bandung, the customer satisfaction of PT Bank BNI Branch Office UPI Bandung, and the influence of the elements of service quality and customer value on customer satisfaction of PT Bank BNI Branch Office UPI Bandung. The method used is a survey method. Data collected through distributing questionnaires to the respondents. The population in this study is lecturers and employees of the Indonesian Education University (UPI) who are customers of Bank BNI Branch UPI, as many as 1,807 people.Â  The results of this study revealed that in general the quality of services in a category well enough, customers benefit from the services offered by banks, and customers feel quite satisfied with the bank services. The study also reveals the quality of customer service and value has a positive influence and significantly to customer satisfaction. This implies that the bank management efforts to improve customer satisfaction can be started from efforts to improve service quality and customer value.